New Approaches to Breast Cancer Screening (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
According to the International Agency for Research on Cancer (IARC, Lyon), breast cancer (breast cancer) is an "ideal" tumor for population screening. This is the most common tumor, especially in women over 50 years old. Out of 10 million . newly detected malignant tumors of various organs in the world account for 10% of the mammary gland. Only in women, breast cancer accounts for 22% of all oncological diseases. In industrialized countries, this figure is even higher - 27%. However, breast cancer is also the most common tumor in developing countries: in 2000, breast cancer was detected in 471,000 women in developing countries, which is more than cervical cancer (379,000), which was the most common cancer until the previous year [1, 2].